2020
DOI: 10.1128/msphere.00846-19
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Observations of an Aperiodic Oscillatory Gliding Behavior in Myxococcus xanthus Using Confocal Interference Reflection Microscopy

Abstract: The deltaproteobacterium Myxococcus xanthus is a model for bacterial motility and has provided unprecedented insights into bacterial swarming behaviors. Fluorescence microscopy techniques have been invaluable in defining the mechanisms that are involved in gliding motility, but these have almost entirely been limited to two-dimensional (2D) studies, and there is currently no understanding of gliding motility in a three-dimensional (3D) context. We present here the first use of confocal interference reflection … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Multi-wavelength IRM was carried out using the same equipment and method as described by Rooney et al in Ref. [10]. The lens specimen was imaged using a confocal microscope set in reflection mode with a 10x/0.3 UPLANFL lens (Olympus, Japan) using 488-nm and 514-nm lasers, and the difference method was applied.…”
Section: Lettermentioning
confidence: 99%
See 1 more Smart Citation
“…Multi-wavelength IRM was carried out using the same equipment and method as described by Rooney et al in Ref. [10]. The lens specimen was imaged using a confocal microscope set in reflection mode with a 10x/0.3 UPLANFL lens (Olympus, Japan) using 488-nm and 514-nm lasers, and the difference method was applied.…”
Section: Lettermentioning
confidence: 99%
“…It has been recently shown that IRM can make use of multiple illumination wavelengths to gain insights into the motility of bacterial cells [10]. The use of additional wavelengths enabled more precise visualization of the position of the cell membrane relative to the glass substrate.…”
mentioning
confidence: 99%
“…Multi-wavelength IRM was carried out using the same equipment and method as described by Rooney et al . [10]. The lens specimen was imaged using a confocal microscope set in reflection mode with a 10x/0.3 UPLANFL lens (Olympus, Japan) using 488 nm and 514 nm lasers, and the difference method was applied.…”
Section: Figmentioning
confidence: 99%
“…It has been recently shown that IRM can make use of multiple illumination wavelengths to gain insights into the motility of bacterial cells [10]. The use of the additional wavelengths enabled more precise visualisation of the position of the cell membrane relative to the glass substrate.…”
mentioning
confidence: 99%
See 1 more Smart Citation